The Correlation Between Students’ Learning Styles and Their Speaking Performance at the Third Semester Students of English Education Study Program of IAIN STS Jambi - Fitria, Wahyuni; Hakim, Luqman (JR-ELT (Journal of Research in English Language Teaching), 2017)
The purpose of this research was: 1) To determine the learning styles of students, 2) to know the correlation between students’ learning style and their speaking performance, and 3) to know the contribution of learning styles toward speaking performance. This research was descriptive quantitative research with statistical analysis techniques using Pearson Product Moment. The collection of data obtained through questionnaires and speaking performance rubric. The results showed the overall look that learning styles at Third Semester of English Education Program of IAIN STS Jambi is a visual 14 students (43.75%), audiovisual 10 students (31.25%), kinesthetic 8 students (25%). And based on the Pearson Product Moment Correlation test, it was known that there was very high correlation between learning style and speaking performance with Pearson Correlation value 0.842 with a significance value 0.000 <0.005 so it can be concluded that there is a significant correlation between learning style and speaking performance. Then, based on the simple linear regression test showed that learning style contributed as much as 7,1% (R Square 0,071) on the speaking performance.